Pengaruh Brand Image, Product Quality dan Brand Ambassador Lee Min Ho terhadap Minat Beli Produk Skincare Sunscreen Azarine di Kecamatan Kota Kediri - Nia Variesta Aprilia; Endah Kurniawati; Nuril Aulia Munawaroh (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This research aims to analyze the influence of brand image, product quality, and brand ambassador Lee Min Ho on consumer buying interest in Azarine sunscreen products in Kediri city district. This study uses a quantitative method with an associative approach. The sampling method employed is Non-Probability Sampling with purposive sampling technique. In this study, data collection was conducted using a questionnaire distributed to 130 respondents. The analytical techniques used in this research include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t-test (partial), F-test (simultaneous), and coefficient of determination test (R2) analyzed using SPSS 26 software. The results show that partially, the brand image variable does not have a significant effect on buying interest, indicated by a significance value of 0.555 > 0.05. The product quality variable partially has a significant effect on purchase interest with a significance value of 0.041 < 0.05, and the brand ambassador variable partially has a significant effect on purchase interest with a significance value of 0.000 < 0.05. Simultaneously, brand image, product quality, and brand ambassador have a positive and significant effect on purchase interest for Azarine sunscreen products in Kediri city district, with a significance value of 0.000 < 0.05. The coefficient of determination value of 0.581 indicates that 58.1% of the variation in consumer purchase interest can be explained by the three variables: brand image, product quality, and brand ambassador, while the remaining 41.9% is influenced by other external factors outside these variables.